Integration of diffusive gradient thin‑film devices and functionalized electrode sensing matrix for discriminative detection of heavy metals in water environments - Cantuária, José Bruno; Mendes, João Vitor; Fugikawa-Santos, Lucas (Materials Research Society, 2024)
This study presents a novel approach combining diffusive gradient thin-film devices and a sensing matrix of functionalized electrodes for discrimination and quantification of heavy-metals in water environments. The experimental setup uses four sensing units with interdigitated gold-plated electrodes and an ionic conductive hydrogel. Impedance measurements were conducted using a gain/phase analyzer in the frequency range from 10 MHz to 0.1 Hz. Principal component analysis was applied to enhance data interpretation. The results showed distinct clusters for cobalt (Co2+) and manganese (Mn2+) ions at concentrations ranging from 10 to 100 ppm, indicating the potential for discrimination between water samples contaminated with these analytes. The integration of IoT and low-cost instruments enables real-time monitoring, wireless transmission of data, and cloud storage. This research contributes to the development of cost-effective methods for heavy metal detection and environmental monitoring, facilitating improved water quality assessment and prompt risk mitigation.
Integration of diffusive gradient thin‑film devices and functionalized electrode sensing matrix for discriminative detection of heavy metals in water environments
Keywords: Sensing matrix; Heavy metal ions; Diffusive gradient thin-film devices; Water environments